Using a visualisation-based and progressive learning environment as a cognitive tool for learning computer programming - Peng, Jun; Wang, Minhong; Sampson, Demetrios; van Merriënboer, Jeroen J. G. (Australasian Journal of Educational Technology, 2019)
Project-based learning (PjBL) has been widely promoted in educational practice, for example, computer programming education. While PiBL may help learners to connect abstract knowledge with authentic practice, the complexity of completing an authentic project may overwhelm learners, making them unable to achieve the desired learning outcomes. This study proposes a visualisation-based and progressive learning environment as a cognitive tool to support PjBL of programming. The cognitive tool is designed to externalise the complex process of completing a realistic programming project. It aims to scaffold the complex project process, foster effective thinking and reflection, and allow the teacher to track and give feedback on individual performance throughout the project process. Moreover, simple-to-complex sequencing of whole-task projects is incorporated into the cognitive tool to support progressive learning with authentic projects. Senior college students participated in this study by completing a project-based programming learning module using the proposed cognitive tool. The results showed that after incorporating the simple-to-complex approach, the visualisation-based cognitive tool is more effective in improving students’ programming performance and better perceived by students in terms of its support for scaffolding and articulating the complex project process.